Trading Water for Carbon: Maintaining Photosynthesis at the Cost of Increased Water Loss During High Temperatures in a Temperate Forest. Issue 1 (17th January 2020) - Griebel, Anne; Bennett, Lauren T.; Metzen, Daniel; Pendall, Elise; Lane, Patrick N.J.; Arndt, Stefan K.
Abstract: Carbon and water fluxes are often assumed to be coupled as a result of stomatal regulation during dry conditions. However, recent observations evidenced increased transpiration rates during isolated heatwaves across a range of eucalypt species under experimental and natural conditions, with inconsistent effects on photosynthesis (ranging from increases to stark declines). To improve the empirical basis for understanding carbon and water fluxes in forests under hotter and drier climates, we measured the water use of dominant trees and ecosystem‐scale carbon and water exchange in a temperate eucalypt forest over three summer seasons. The forest maintained photosynthesis within 16% of baseline rates during hot and dry conditions, despite 70% reductions in canopy conductance during a 5‐day heatwave. While carbon and water fluxes both decreased by 16% on exceptionally dry days, gross primary productivity only decreased by 5% during the hottest days and increased by 2% during the heatwave. However, evapotranspiration increased by 43% (hottest days) and 74% (heatwave), leading to 40% variation in traditional water use efficiency (water use efficiency = gross primary productivity/evapotranspiration) across conditions and approximately two‐fold differences between traditional and underlying or intrinsic water use efficiency on the same days. Furthermore, the forest became a net source of carbon following a 137% increase in ecosystem respiration during the heatwave, highlighting that the potential for temperate eucalypt forests to act as net carbon sinks under hotter and drier climates will depend not only on the responses of photosynthesis to higher temperatures and changes in water availability, but also on the concomitant responses of ecosystem respiration. Key Points: GPP of temperate eucalypts varied by up to 16% compared with up to 74% variation in ET during hot and dry periods and during a heatwave WUE estimates for the same period differed up to twofold depending on the way it was calculated Doubling of ecosystem respiration turned the forest from a net sink into a net source of carbon during a longer heatwave